A Implementation of an Expert System for Diagnosing Attention Deficit Hyperactivity Disorder (ADHD) in Adults Using the Forward Chaining and Certainty Factor Methods Based on a Web Platform: IMPLEMENTASI SISTEM PAKAR UNTUK MENDIAGNOSA GANGGUAN ATTENTION DEFICIT HYPERACTIVITY DISORDER (ADHD) PADA ORANG DEWASA MENGGUNAKAN METODE FORWARD CHAINNING DAN CERTAINTY FACTOR BERBASIS WEB (STUDI KASUS: MAHASISWA UNPAM) - Abdallah, Zidan Absar; Sutresna, Jaka (Teknik Informatika Universitas Pamulang, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder that may persist into adulthood, affecting concentration, impulse control, and daily activities. This research aims to develop a web-based expert system to assist in early screening of ADHD in adults, particularly students at Pamulang University, using the Forward Chaining and Certainty Factor methods. Forward Chaining is applied as an inference mechanism to determine ADHD type based on symptoms, while the Certainty Factor method calculates the confidence level of the diagnosis using expert and user certainty values. The results of Black Box Testing show that all system functions work properly and produce accurate initial diagnostic results. This system is expected to help increase awareness of mental health among students and serve as a digital-based early detection tool for ADHD.